Tecnologia assistiva e perfil funcional dos alunos com deficiência física nas salas de recursos multifuncionais - Queiroz, Fernanda Matrigani Mercado Gutierres de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The educational inclusion is worried about the learning of all the student who confronts barriers to participate effectively of the school life. In the perspective of the inclusive education the student who presents some deficiency must preferential be taken care of in common education and the special education offers the educational attendance specialized to complement its educational necessities. In this context the objective of the research shows: To analyze if the available resources of Assistive Technology in the rooms of multi-functional resources take care of the functional demand of the students with physical deficiency, according to vision of the teacher of the Specialized Educational Attendance. The study included teachers responsible for multi-purpose facilities that serve students with disabilities. For data collection the research were used instruments School Function Assessment, questionnaire of Assistive Technology for Education II and interview semi structuralized with the professors of the educational attendance specialized to identify the adequacies necessary in accordance with the specifics functional profile of the students. The collected data had been dealt with and analyzed according to analysis content and, in the sequence, carried through the triangulation of the data with the information of the three instruments already mentioned. The speech of the interviews had been organized as a descriptive summary and the information of the three collection instruments had been organized into a single document, with triangulation of data, which was analyzed according to content analysis being presented the nine categories that were generated: 1) Mobility and accessibility; 2) Movable available and used by the pupils; 3) Participation and aid in the performance of tasks; 4) Prepare and to clean 5) Pedagogical didactic material available and used by the students; 6) Use of materials; 7) Use of the computer and equipment; 8)...

A inclusão educacional se preocupa com a aprendizagem de todos os alunos que enfrentam barreiras para participar efetivamente da vida escolar. Na perspectiva da educação inclusiva o aluno que apresenta alguma deficiência deve ser atendido preferencialmente no ensino comum e a educação especial oferece o atendimento educacional especializado para complementar suas necessidades educacionais. Neste contexto revela-se o objetivo da pesquisa: Analisar se os recursos de Tecnologia Assistiva disponíveis nas salas de recursos multifuncionais atendem a demanda funcional dos alunos com deficiência física, segundo a visão dos professores do Atendimento Educacional Especializado. Participaram do estudo os professores responsáveis pelas salas de recursos multifuncionais que atendem alunos com deficiência física. Para coleta dos dados da pesquisa foram utilizados os instrumentos School Function Assessment, questionário de Tecnologia Assistiva para Educação II e entrevista semiestruturada com os professores do atendimento educacional especializado para identificar as adequações necessárias para atender as especificidades de acordo com o perfil funcional dos alunos. As falas das entrevistas foram organizadas em forma de síntese descritiva e as informações dos três instrumentos de coleta foram organizadas em um documento único, triangulação dos dados, que foi analisado segundo a análise de conteúdo sendo apresentadas as nove categorias geradas que foram: 1) Mobilidade e acessibilidade; 2) Mobiliários disponíveis e utilizados pelos alunos; 3) Participação e auxílio no desempenho de tarefas; 4) Preparar e limpar 5) Material didático-pedagógico disponível e utilizado pelos alunos; 6) Uso de materiais; 7) Uso do computador e equipamentos; 8) Trabalho escrito; 9) Comunicação funcional. Concluiu-se que somente os recursos de Tecnologia Assistiva que constam no kit do Ministério da Educação para a sala de recursos atendem...
Keywords: Educação especial; Equipamentos de autoajuda para deficientes; Deficiência física; Inclusão em educação; Special education